2019
DOI: 10.1002/ece3.5223
|View full text |Cite
|
Sign up to set email alerts
|

Carbon sequestration and soil restoration potential of grazing lands under exclosure management in a semi‐arid environment of northern Ethiopia

Abstract: Exclosures are used to regenerate native vegetation as a way to reduce soil erosion, increase rain water infiltration and provide fodder and woody biomass in degraded grazing lands. Therefore, this study assessed the impact of grazing exclosure on carbon sequestration and soil nutrients under 5 and 10 years of grazing exclosures and freely grazed areas in Tigray, northern Ethiopia. Carbon stocks and soil nutrients increased with increasing grazing exclusion. However, open grazing lands and 5 years of grazing e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 57 publications
3
26
0
Order By: Relevance
“…However, previous study from Inner Mongolia grasslands finding that soil pH increased and became more neutral with the increase of enclosure time (Ma et al, 2016). What's more, we further found that PSME could increase soil nutrients significantly than PSM, including soil total C, total N, total P and available N contents (P < 0.05), which was agreement with the studies about grassland from Xiong et al (2016) and Gebregergs et al (2019). The increase in total C and total N concentrations might be mainly ascribed to the undergrowth vegetation recovery, accumulation of litter and increase in soil nutrient return in PSME (Table 1), and changes in the "quality" and "quantity" of litter lay an important role in affecting the soil nutrient (Rajr et al, 2006).…”
Section: Effects Of Afforestation Combined With Enclosure Management supporting
confidence: 92%
See 2 more Smart Citations
“…However, previous study from Inner Mongolia grasslands finding that soil pH increased and became more neutral with the increase of enclosure time (Ma et al, 2016). What's more, we further found that PSME could increase soil nutrients significantly than PSM, including soil total C, total N, total P and available N contents (P < 0.05), which was agreement with the studies about grassland from Xiong et al (2016) and Gebregergs et al (2019). The increase in total C and total N concentrations might be mainly ascribed to the undergrowth vegetation recovery, accumulation of litter and increase in soil nutrient return in PSME (Table 1), and changes in the "quality" and "quantity" of litter lay an important role in affecting the soil nutrient (Rajr et al, 2006).…”
Section: Effects Of Afforestation Combined With Enclosure Management supporting
confidence: 92%
“…The increase in total C and total N concentrations might be mainly ascribed to the undergrowth vegetation recovery, accumulation of litter and increase in soil nutrient return in PSME (Table 1), and changes in the "quality" and "quantity" of litter lay an important role in affecting the soil nutrient (Rajr et al, 2006). Identically, results of the impact of grazers on birch forest demonstrated that aboveground carbon stocks were higher in the long-term absence of sheep than in the continual presence of high sheep densities (Gebregergs et al, 2019).…”
Section: Effects Of Afforestation Combined With Enclosure Management mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the correlations between plant community diversity and soil physicochemical properties differed among the four sites (Supplementary Tables 3A,B). This finding is similar to the results of many studies in which the correlations between plant communities and soil physicochemical properties were not uniform across different grassland types and utilization patterns (Herrero-Jáuregui and Oesterheld, 2017;Fayiah et al, 2019;Gebregergs et al, 2019).…”
Section: Effects Of Utilization Mode On Grassland Soil Physicochemical Propertiessupporting
confidence: 90%
“…Some respondents pointed out that the grass inside our exclosures looked like it used to look like earlier, and that this is the preferred pasture status. Long-term studies of community exclosures in Northern Ethiopia show an increase in field layer biomass and species diversity (Mekuria et al 2018;Gebregergs et al 2019). We found a small difference in species composition, likely caused by the differential palatability of the species; e.g.…”
Section: Field Layer Cover and Species Compositionmentioning
confidence: 66%